2014
DOI: 10.1016/j.vetpar.2014.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel topical combination of fipronil, (S)-methoprene, eprinomectin and praziquantel against feline urinary bladder worm (Capillaria plica) infection

Abstract: Infection with urinary capillarid bladder worms has been observed in cats worldwide. Although considered as generally causing no or little harm, infection with urinary capillarids may be associated with clinical disease which requires an appropriate treatment including the use of anthelmintics. Therefore, the efficacy of a novel topical combination formulation of fipronil 8.3% (w/v), (S)-methoprene 10% (w/v), eprinomectin 0.4% (w/v), and praziquantel 8.3% (w/v) (BROADLINE(®), Merial) was evaluated against urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…As Broadline®, a topical combination product containing fipronil, (S)-methoprene, eprinomectin and praziquantel, was demonstrated to be efficacious against urinary capillariasis (Knaus et al 2014c) and treatment resulted in >99 % reduction of faecal capillarid egg counts in a field setting (Rehbein et al 2014), the controlled study reported here was conducted to evaluate the efficacy of this product against infections of C. aerophila in cats.…”
Section: Introductionmentioning
confidence: 99%
“…As Broadline®, a topical combination product containing fipronil, (S)-methoprene, eprinomectin and praziquantel, was demonstrated to be efficacious against urinary capillariasis (Knaus et al 2014c) and treatment resulted in >99 % reduction of faecal capillarid egg counts in a field setting (Rehbein et al 2014), the controlled study reported here was conducted to evaluate the efficacy of this product against infections of C. aerophila in cats.…”
Section: Introductionmentioning
confidence: 99%
“…Pearsonema plica) (Eckert et al 2005) belongs to the Capillariidae family (http://www.ncbi.nlm.nih.gov). It occurs worldwide in carnivores, mostly in wild animals (foxes, wolves) (Knaus et al 2014;Krone et al 2008). This infection is rarely reported in domestic carnivores.…”
mentioning
confidence: 99%
“…Considering that female parasites only periodically excrete eggs, it is not always possible to set a diagnosis this way, despite the presence of infection (Kirkpatrick and Nelson, 1987). Since egg excretion varies and the sensitivity of the urine sediment examination is low, more than one urine sediment examination is recommended (Knaus et al, 2014). Definite diagnosis is set through endoscopy, or more often via detection of eggs in the urine sediment (Basso et al, 2014).…”
Section: Diagnosismentioning
confidence: 99%
“…Basso et al (2014) stated that treatment with fenbendazole and ivermectin caused short-term improvement, while levamizole, metabolites of which are excreted by the urine in 94% of cases, was more effective (Studzińska et al, 2015). Knaus et al (2014) studied the treatment effectiveness of a drug combination: fipronil 8.3% (w/v), methoprene 10% (w/v), eprinomectin 0.4% (w/v) and praziquantel 8.3% (w/v) for treatment of cat urinary capillariosis (Studzińskaet al, 2015). The study involved sixteen shorthaired European cats (5 male, 11 female) in which urine C. plica eggs were diagnosed before treatment (Knaus et al, 2014).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation